2004
DOI: 10.1210/jc.2004-0126
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Deficiency Predicts Cardiovascular Risk in Young Adults Treated for Acute Lymphoblastic Leukemia in Childhood

Abstract: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy, and until recently prophylactic cranial radiotherapy (CRT) was important for achieving longterm survival. Hypothalamic-pituitary hormone insufficiency is a well-recognized consequence of CRT for childhood cancer. Another problem is increased cardiovascular risk, which has been shown in long-term survivors of other childhood cancers. In the only previously reported study on cardiovascular risk after childhood ALL, obesity and dyslipidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
176
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(197 citation statements)
references
References 45 publications
15
176
3
3
Order By: Relevance
“…Large waist circumference is a strong independent risk factor for insulin resistance, 38,39 and untreated GH deficiency is associated with an array of unfavorable cardiovascular risk factors and outcomes 23,24,[40][41][42][43] and may also be a risk factor for insulin resistance. 13,23,44,45 The risk profile for diabetes that we observed in ALL survivors with GH deficiency is notable. Whether or not GH treatment is advisable for GH-deficient ALL survivors 19,46 is beyond the scope of our study, but assessment of hypothalamus and pituitary functioning and GH secretion among ALL survivors appears warranted, even in those who did not receive cranial irradiation, given that 20% of those subjects were found to be GH-deficient.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Large waist circumference is a strong independent risk factor for insulin resistance, 38,39 and untreated GH deficiency is associated with an array of unfavorable cardiovascular risk factors and outcomes 23,24,[40][41][42][43] and may also be a risk factor for insulin resistance. 13,23,44,45 The risk profile for diabetes that we observed in ALL survivors with GH deficiency is notable. Whether or not GH treatment is advisable for GH-deficient ALL survivors 19,46 is beyond the scope of our study, but assessment of hypothalamus and pituitary functioning and GH secretion among ALL survivors appears warranted, even in those who did not receive cranial irradiation, given that 20% of those subjects were found to be GH-deficient.…”
Section: Discussionmentioning
confidence: 78%
“…Of the 8 cases with indicators of metabolic syndrome, 4 received cranial radiation and 4 did not. Similarly, Link et al 13 evaluated GH deficiency and cardiovascular risk fac-tors in 44 adult survivors of childhood ALL, all of whom were treated with cranial irradiation. They found that all subjects, using the same cutoff points as in our study, were either GH-deficient (91%) or GH-insufficient (9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each patient was matched with a control subject, which was randomly selected from a computerized population register described elsewhere, similar in age, sex, residence (rural/non-rural), and smoking habits (16). Among female controls, seven used oral contraceptives, all with a combination of 35 mg ethinyl E 2 and 250 mg levonorgestrel or up to 0.75 mg norethisterone, and one control was postmenopausal and without sex steroid substitution.…”
Section: Controlsmentioning
confidence: 99%